Parent-implemented language intervention for late talkers: a scoping review - Tukiran, Nur Hanisah; Mohamed Zain, Nor Azrita; Ahmad Nordin, Natrah; Ahmad Basri, Nadzirah (National University of Malaysia Press (UKM Press), 2023)
Parent-implemented language intervention (PILI) is one of the intervention approaches used in managing late talkers (LTs). Yet, there are few evidence-based PILI programs available for parents of LTs. This scoping review aimed to (a) assess the characteristics of participants depicted in the literature related to PILI programs for parents of LTs, (b) provide an overview of the structure and design of the available PILI programs for parents of LTs, and (c) explore the effectiveness of the programs in relation to the characteristics of reviewed studies. The scoping review was performed by adhering to the general principles prescribed by Arksey and O’Malley (2005). Articles that fulfilled the inclusion criteria and were published from 1980 to 2018 were selected. Two reviewers independently charted the information from the identified articles. A total of 15 articles were selected. The results were reviewed in terms of participant characteristics, intervention characteristics, and effectiveness of PILI programs. Most adult participants in PILI studies were mothers and included child participants with either expressive language delay or receptive and expressive language delay. Moreover, there were different structures and designs of PILI programs for parents of LTs. Preliminary evidence indicated that PILI was more effective than no/delayed intervention and could be as effective as direct therapy provided by clinicians. A discussion related to the findings was also presented.